2020
DOI: 10.20493/birtop.818308
|View full text |Cite
|
Sign up to set email alerts
|

Readiness and Views of the Students Who Have Just Enrolled University towards Distance Education due to the Pandemic

Abstract: Bu çalışmada normalde yüz yüze eğitim veren bir üniversiteyi yeni kazanmış öğrencilerin pandemi kaynaklı uzaktan eğitime ilişkin hazırbulunuşluk düzeyleri incelenmiş ve sürece yönelik görüşleri alınmıştır. Çalışma grubunu bir devlet üniversitesinde eğitim fakültesine yeni kayıt yaptırmış olan 305 1. sınıf öğrencisi oluşturmaktadır. Karma araştırma yaklaşımının benimsendiği bu çalışmada, nicel verilerin çözümlenmesinde betimsel analiz, nitel verilerin çözümlenmesinde ise içerik analizi kullanılmıştır. Çalışmanı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Looking at other prominent findings, the context of distance education and socialization can be discussed. In addition to being seen as an element that eliminates social distance (Sindiani et al, 2020), distance education is also thought to negatively affect socialization (Genç & Gümrükçüoğlu, 2020;Kuzu, 2020). As emphasized by Başaran et al (2020), these problems stand out as an important difference in distance education, when the socialization possibilities of face-to-face education are kept in mind.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Looking at other prominent findings, the context of distance education and socialization can be discussed. In addition to being seen as an element that eliminates social distance (Sindiani et al, 2020), distance education is also thought to negatively affect socialization (Genç & Gümrükçüoğlu, 2020;Kuzu, 2020). As emphasized by Başaran et al (2020), these problems stand out as an important difference in distance education, when the socialization possibilities of face-to-face education are kept in mind.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…examined, it was reported that the distance education system had the most appropriate conditions that could be applied during the pandemic period. In the literature, some studies support this view, stating that it is an appropriate decision to implement distance education during the pandemic period (Kuzu, 2020). Besides, it was stated that the efficiency of the theoretical course was high in the education given, and the hybrid system was adopted in the applied courses.…”
Section: Discussionmentioning
confidence: 99%
“…When the studies are examined in general, it is seen that teachers and academicians have technical and technological difficulties in distance education, the workload increases in the lesson planning process, worried about measurement and evaluation, inadequate in using effective teaching methods that will attract the attention of the students (Fauzi & Khusuma, 2020;Luongo, 2018). Looking at the problems experienced in distance education from the point of view of students, it is seen that students mostly complain about the lack of communication during the lesson and they expect instructors to come to the lesson prepared (Karatepe et al, 2020;Y. Kuzu, 2020).…”
Section: Inesjournal (The Journal Of International Education Science)mentioning
confidence: 99%